Cultivating Digital Readiness and How Employee Perceptions, Trust, and Risk Influence Technology Adoption Intentions Through Attitude in the Workplace - Nursahdi Saleh; Muhammad Sain; Samsul Bahri (Al-Qalam Institute, 2025)
This study examines how employee perceptions, trust, and risk influence technology adoption intentions through attitude, with digital readiness as a moderating variable in the context of higher education institutions. Using the Unified Theory of Acceptance and Use of Technology (UTAUT) as a theoretical foundation, the research applies a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) on data collected from 195 employees. The findings reveal that employee perception, trust, and risk significantly influence both attitude and technology adoption intention, with attitude serving as a full mediator. Conversely, digital readiness does not significantly moderate the relationship between attitude and adoption intention, suggesting that technical capability alone does not enhance behavioral outcomes without psychological commitment. The study reinforces the importance of attitudinal and cognitive factors in driving digital transformation and provides practical implications for higher education management to strengthen trust, manage perceived risk, and cultivate positive perceptions to foster sustainable digital engagement among employees.